Immunotoxic properties of insacar - A. A. Stepanov (Российский паразитологический журнал, 2016)
Immunotoxic properties of insacar are studied. By the results of reaction of hypersensitivity of the sloweddown type the stimulation index at the animals receiving insacar at the dose of 0,02 and 0,2 ml made respectively 9,45 and 9,79 unlike 10,18 in control that allows to conclude that the drug doesn't oppress the T-cellular link of immune system. Single application of insacar on skin in therapeutic and ten times increased therapeutic doses has no negative effect on the humoral immune answer.